Trends and Themes in Financial Intermediation Research: A Bibliometric Approach - Indriarti, Resti; Sari, Maya; Waspada, Ika Putera (Business Education Program of Universitas Pendidikan Indonesia, 2024)
This research was designed to examine research developments and look for research gaps regarding Financial Intermediation through a bibliometric analysis approach using VOS Viewer. The Publish or Perish application is used to retrieve the Google Scholar database in order to fulfill research data. The title of the article is used to guide the search process based on the keyword